An analysis of the influence exerted by the pharmacist and pharmacy assistant in the purchase decision of health and beauty aid products - Suttner, Raymond Sharl (Rhodes University, Faculty of Commerce, Department of Management, 1986)
[Introduction] The 1980s have ushered in an era of extreme competitive pressure for the modern business organisation. In previous times many business organisations have succeeded simply because of the excellence of their products, with little concern or attention being paid to the wants and needs of potential customers. As the business environment has become more competitive, however, the point of focus has changed. There is ample evidence which suggests a correlation between success in business and firms which have adopted a marketing-orientated philosophy of business. The evolution of marketing as a discipline has been hastened in recent times by the need of the firm to survive in the face of increasing competition. This "increasing attention" is occurring because of the realisation that sheer product excellence alone will not necessarily mean that the firm will succeed in establishing a group of satisfied customers in the long term. It is the adoption of the so-called "marketing concept" which provides the opportunity for the firm to develop a competitive edge which will more likely eventuate in success.
Keywords: Cosmetics -- Marketing; Consumer behavior; Pharmacists -- Information services; Drugstores -- Marketing